The mediator complex subunits MED25/PFT1 and MED8 are required for transcriptional responses to changes in cell wall arabinose composition and glucose treatment in Arabidopsis thaliana - Seguela-Arnaud, Mathilde; Smith, Caroline; Castellanos Uribe, Marcos; May, Sean; Fischl, Harry; McKenzie, Neil; Bevan, Michael W. (BioMed Central, 2015)
Background: Plant cell walls are dynamic structures involved in all aspects of plant growth, environmental interactions and defense responses, and are the most abundant renewable source of carbon-containing polymers on the planet. To balance rigidity and extensibility, the composition and integrity of cell wall components need to be tightly regulated, for example during cell elongation.